Oleuropein/ligstroside isomers and their derivatives in Portuguese olive mill wastewaters - Cardoso, Susana M. (2011)
Olive mill wastewaters (OMW) are a potential source of biophenols, but they have a complex composition with many unknown phenolics. The analysis of purified methanol extracts from two Portuguese OMW by electrospray mass spectrometry in the negative mode showed [M-H]- ions at m/z 539 and m/z 523, corresponding respectively to oleuropein and ligstroside isomers which contain the glucose unit linked to its aromatic moiety. Also, the fragmentation pathway of the [M-H]- ions at m/z 863, 685 and 847 indicated the presence of a diglucoside derivative of the oleuropein isomer and of mono- and diglucosides of the ligstroside isomer, respectively. Moreover, the two OMW samples contained an elenoic derivative of the ion at m/z 685 and a degradation product (m/z 453) of the [M-H]- ion at m/z 523. Future studies focusing on the abundance of these compounds on OMW, as well as their bioactivities, will determine their possible industrial exploitation.